ヒガシ オングルトウ トウブ ノ セッケイ ノ ユウカイ - 林, 正久; ハヤシ, マサヒサ; Hayashi, Masahisa (国立極地研究所, 1977)
P(論文) 第16次南極観測隊員として,1975年12月12日から1976年2月15日まで,昭和基地南東部の一流域を選び,雪渓の融水流の測定を行った.この流域は,雪渓の融水によって涵養されている.調査期間中に,4.8×10^3 tonの雪が消失し,そのうち3.1×10^3 tonが融水流として観測された.このことは,極地露岩地域の雪渓の消耗は,主として融水流の形をとるということができる.気候要素との関係をみてみると,気温が氷点以上になることが多かった1月上・中旬は,雪渓の消耗量は気温に影響され,氷点を越えることの少ない1月下旬以降は,日射量の変化が流出量を左右しているといえる. Measurement of meltwater from snow patches was made in a small drainage basin near Syowa Station, East Ongul Island, Antarctica, during the period from December 12, 1975 to February 15, 1976, in order to obtain basic data for wastage of ice masses. 4.8×10^3 tons of snow disappeared from the basin during the observation period. Amount of meltwater was measured to be 3.1×10^3 tons in the same period. This fact may indicate that melting accounts for a quite large portion of wastage of snow catches in ice-free areas of polar regions. Investigation on the relationship between climatic elements and wastage showed that the amount of wastage depends mainly on the air temperature from January 1 to 19 when the temperature often exceeds the freezing point, but on solar radiation during the period from January 26 to February 15 when temperature rarely exceeds the freezing point. departmental bulletin paper